Fish, funding, and food systems: a review of the U. S. Department of Agriculture’s recent history of grant funding in support of the seafood sector (2018–2023) - Stoll, Joshua S.; Advani, Sahir; Dubovsky, Elizabeth; Grinnell, Willow; Oyikeke, Tolulope S. (Frontiers in Sustainable Food Systems, 2025)
IntroductionSeafood is an important source of healthy animal protein, making it a valuable part of the food system in the United States.MethodsWe assembled a database of 146,720 grants awarded by the U.S. Department of Agriculture (USDA) from 2018 to 2023. Our database included all grants awarded by the four USDA agencies primarily responsible for grant-making activities designed to enhance domestic food systems. We reviewed the extent to which these grants have supported the seafood sector, including wild capture fisheries and aquaculture. Using interviews with individuals involved in different dimensions of the seafood economy that have applied for USDA grants, we augment our review.ResultsOf the $31.2 billion in funding awarded, only $261.7 million (n = 768) went to support projects associated with the seafood sector, representing 0.52% of the grants during the 6-year study period. Our analysis shows USDA’s recent grant portfolio has included projects related to aquatic and marine foods, but that overall funding has been limited.DiscussionOur review offers insights into why USDA funding is important to the seafood sector, barriers that are limiting the seafood sector’s access to USDA grants, and recommendations for how to better support the seafood sector moving forward.